2008
DOI: 10.1109/tbme.2007.912638
|View full text |Cite
|
Sign up to set email alerts
|

Manufacture of Passive Dynamic Ankle–Foot Orthoses Using Selective Laser Sintering

Abstract: Ankle-foot orthosis (AFO) designs vary in size, shape, and functional characteristics depending on the desired clinical application. Passive Dynamic (PD) Response ankle-foot orthoses (PD-AFOs) constitute a design that seeks to improve walking ability for persons with various neuromuscular disorders by passively (like a spring) providing variable levels of support during the stance phase of gait. Current PD-AFO manufacturing technology is either labor intensive or not well suited for the detailed refinement of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
122
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(129 citation statements)
references
References 21 publications
1
122
0
1
Order By: Relevance
“…[17][18][19] The present study is the first one to (i) assess the effectiveness of SLS-AFO on drop foot gait and (ii) compare SLS-AFOs' clinical performance to clinical performance achieved using custom-moulded PP-AFOs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[17][18][19] The present study is the first one to (i) assess the effectiveness of SLS-AFO on drop foot gait and (ii) compare SLS-AFOs' clinical performance to clinical performance achieved using custom-moulded PP-AFOs.…”
Section: Resultsmentioning
confidence: 99%
“…In literature, there is evidence to support the use of additive manufacturing for producing orthotic or prosthetic devices. [13][14][15][16][17][18][19] However, issues related to material properties and manufacturing costs still need to be investigated before additive technologies could be considered ready for clinical use. Furthermore, it is not clear to the authors how much evidence is necessary before one can consider these manufacturing technologies 'ready for commercial' use.…”
Section: Barefoot Gait (Sdmentioning
confidence: 99%
“…Clinical prescription of strut stiffness was based on the patient's available range of motion (ROM), activity level, types of activities performed, body mass, and active duty status (ie, indicating that they would carry heavy loads on a regular basis). All struts were initially designed in SolidWorks (Waltham, MA, USA) and constructed from Unfilled Nylon 11 powder (PA D80-ST; Advanced Laser Materials, Temple, TX, USA) using a selective laser sintering technique previously described [13,35]. Mechanical testing performed before biomechanical testing ensured the struts were within 5% of their intended stiffness.…”
Section: Methodsmentioning
confidence: 99%
“…The authors concluded respectively that the materials used were highly useful in metallic appearance modelling (polyamide containing Al) and in direct tissue engineering applications (Ti6Al4V). Similarly, the paper by Faustini et al [50] in 2008 demonstrated the feasibility of XCT and AM in production of customised orthoses, although the authors chose in this instance to base a series of SLS orthoses on XCT data of an existing carbon fibre model instead of designing their product in direct reference to patient data. The authors compared AM orthoses of different materials to the traditionally manufactured carbon fibre reference, concluding that the method presented considerable promise for the field.…”
Section: History 2005-2010mentioning
confidence: 99%